A Novel Protective Strategy on High‐Voltage LiCoO2 Cathode for Fast Charging Applications: Li1.6Mg1.6Sn2.8O8 Double Layer Structure via SnO2 Surface Modification. Issue 11 (11th July 2019) - Wang, Mengcheng; Feng, Xuyong; Xiang, Hongfa; Feng, Yuezhan; Qin, Changdong; Yan, Pengfei; Yu, Yan
Abstract: Surface corrosion from electrolyte and reconstruction of layer‐structure LiCoO2 are the most important reasons for capacity decay and charging kinetics limitation. Spinel‐type material forms on the surface of LiCoO2 after cycling, which is more stable than the layer‐structure. To stabilize the surface and suppress the reconstruction, double layer structure Li1.6 Mg1.6 Sn2.8 O8 matching LiCoO2 well is introduced to protect Mg‐doped LiCoO2 and restrain the structure change. With a simple surface coating of SnO2 and further high temperature treatment, Mg 2+ in LiCoO2 and partly Li + are extracted out and reacted with SnO2 to form double layer Li1.6 Mg1.6 Sn2.8 O8 . Meanwhile, Co 3+ in pristine LiCoO2 is partly oxidized and electronic conductivity enhanced after surface modification. The Li1.6 Mg1.6 Sn2.8 O8 coating efficiently stabilizes the surface structure of LiCoO2, with less structure change, less cracks appearing on the surface, and much better cycling performance. In addition, stable surface and higher electronic conductivity of LiCoO2 lead to better rate performance. Abstract : Double‐layer Li1.6 Mg1.6 Sn2.8 O8 matching LiCoO2 well is introduced to protect Mg‐doped LiCoO2 by a simple surface coating of SnO2 . Mg 2+ in LiCoO2 and partly Li + are extracted out and reacted with SnO2 to form double‐layer Li1.6 Mg1.6 Sn2.8 O8 during thermal treatment. The Li1.6 Mg1.6 Sn2.8 O8 coating efficiently enhances the rate capability and cycling stability of high‐voltage LiCoO2 for fast‐charging applications.